Integrating Sex Education in Fiqh and Natural Science Subjects at Madrasah Ibtidaiyah - Tasliyatul Muhimmah; Miftahuddin Miftahuddin (Prodi PGMI IAIN Salatiga, 2021)
Sex education is not independent as a specific subject in formal education, but its material or content can be found in some subjects, such as Fiqh for the 5th Grade in the chapter of menstruation and khitan, and Natural Science for the 6th Grade in the chapter of human development and growth. This research aimed at knowing the lesson plan, their implementation, and the participation of the school committee in the implementation of sex education. This research used the qualitative method through interviews and documentation in collecting the data. The results showed that most of the teachers of the two subjects have compiled lesson plans but have not implemented them optimally, and there is no participation of the school committee in the implementation of sex education.